Evaluation of woman‐centred care status by Iranian midwives and providing strategies to improve women‐centred care: A sequential explanatory mixed method study protocol - Sepideh Mashayekh‐Amiri; Roghaiyeh Nourizadeh; Sakineh Mohammad‐Alizadeh‐Charandabi; Maryam Vaezi; Shahla Meedya; Mojgan Mirghafourvand (Wiley, 2023)
Abstract Aim The present study aimed to evaluate the status of WCC provided by Iranian midwives. Design A sequential explanatory mixed method study protocol. Methods The present study was conducted in three phases: quantitative, qualitative and mixed. The first phase is a cross‐sectional study that will be performed on midwives working in health centres, public and private hospitals in Iranian. The second phase is a qualitative study, in which purposeful sampling will be used, meaning that the midwives who are part of the extreme cases according to the results of quantitative phase and are willing and able to express their own experiences regarding WCC will be selected. Also, pregnant and parturient women under their cover will also be interviewed. Finally, in the mixed phase, we will use a combination of two quantitative and qualitative studies, a literature review and expert opinion using a Delphi method to provide strategies to improve and promote WCC in midwives. Results Achieving this goal is expected to provide positive outcomes such as strengthening the midwives professional relationship with women and reducing health care costs. No Patient or Public Contribution.